The reflection of tecnologys in construction and deconstruction of society - Oliveira, Malize Lourdes de; Tybusch, Jerônimo Siqueira; Araújo, Luiz Ernani Bonesso de; Medeiros, Liziany Müller (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Study in order to reflect on the main reflections of the technologies in the construction and deconstruction of society. The guiding question sought to reflect the extent to which technologies contribute to the construction and deconstruction of society. Resorted to literature with dialectical approach. Technology can contribute to building a more just society by developing the ability to access, adapt and create new knowledge and social possibilities. As seen, those who are not willing to understand and make use of the computer, run the risk of being excluded, including and especially the world of work. It was concluded that technologies influence society in every way, is education, labor, environment, health, and especially in interpersonal relationships.